From the Editors - Yang Kuang; Ying-Cheng Lai; Zhiming Zheng (Mathematical Biosciences and Engineering)
It is easy to argue that we are entering a new golden era of science and engineering. The predominant approach of conducting timely and in-depth scientic research is forever changed from cycles of simple experiment and theory to cycles thatcombine of experiment, theory, mathematical modeling, and analysis. The landscape of science is now clearly dominated by the peaks of biosciences. Integrativeand interdisciplinary research in life sciences and engineering is no longer merely aslogan but aggressively and collectively pursued and practiced by researchers. Thisshift of paradigms greatly enhances the central importance of mathematical andcomputational modeling and analysis in scientic and engineering endeavors. Withthis exciting backdrop in mind, the American Institute of Mathematical Sciences(AIMS) and Beihang University have decided to launch a joint international journalon mathematical biosciences and engineering. This journal will maximally serve thescientic communities in both developed and developing countries.For more information, please click the 'full text' above.